REFLEXII ȘI CONSTATĂRI PRIVIND UNITATEA NAȚIONALĂ ȘI LIBERTATEA DE CONȘTIINȚĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Reflections and Findings on National Unity and the Freedom of ConscienceThe present study aims to be a critical and reflective radiography on the national independence concepts in the celebration year of the Great Union Centenary, the dangers that erode the national unity and the challenges which the Romanian national state must face in the context in which its sacred and democratic composition principles are distorted by the practical way in which the constitutional and legal enforcements are highlighted.